2014
DOI: 10.1155/2014/764898
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Enzymatic Saccharification of Alkali Pretreated Parthenium sp. Using Response Surface Methodology

Abstract: Parthenium sp. is a noxious weed which threatens the environment and biodiversity due to its rapid invasion. This lignocellulosic weed was investigated for its potential in biofuel production by subjecting it to mild alkali pretreatment followed by enzymatic saccharification which resulted in significant amount of fermentable sugar yield (76.6%). Optimization of enzymatic hydrolysis variables such as temperature, pH, enzyme, and substrate loading was carried out using central composite design (CCD) in response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 24 publications
2
35
0
3
Order By: Relevance
“…Different cellulase enzymes vary in their tolerance to pH and temperature. However, the observations from this study are consistent with the findings of Pandiyan et al (2014), who studied the combined effects of pH and temperature on the enzymatic saccharification of alkali-pretreated Parthenium spp. using response surface methodology.…”
Section: Effect Of Experimental Factors (Ph and Temperature)supporting
confidence: 92%
See 1 more Smart Citation
“…Different cellulase enzymes vary in their tolerance to pH and temperature. However, the observations from this study are consistent with the findings of Pandiyan et al (2014), who studied the combined effects of pH and temperature on the enzymatic saccharification of alkali-pretreated Parthenium spp. using response surface methodology.…”
Section: Effect Of Experimental Factors (Ph and Temperature)supporting
confidence: 92%
“…This was believed to be due to the progressive thermal denaturation of the enzymes at 60 and 70 o C. Studies previously conducted on the effect of temperature on the rate of enzymatic reactions confirmed that when the temperature was higher than the tolerance limit of an enzyme system, the protein structures that maintain the shape and function of the enzyme will become denatured, and this will result in the loss of the enzyme activity (Martinek 1969). Pandiyan et al (2014) optimized the enzymatic saccharification of alkali-pretreated Parthenium spp. using response surface methodology and achieved 83.27% saccharification efficiency at 50 o C, which was higher than 22.16% saccharification efficiency recorded at 60 o C. These were indications that the temperature of 50 o C was the most favored temperature for the enzymatic saccharification of different lignocellulosic biomass.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…This might be due to the adaptability of cellulase complex for the temperature range from 30˚C to 60˚C which was selected in this study. However, there was slightly decreased in enzymatic hydrolysis efficiency at temperature beyond 50˚C, this could partially be explained by the loss of enzyme activity due to thermal inactivation [19]. It is observed that the highest sugar concentration was produced at the range of pH 6 to pH 7 and 40˚C to 50˚C, where this result is also found in study of Ong et al (2012) by using rice straw as substrate [20].…”
Section: Interaction Between Parameterssupporting
confidence: 52%
“…RSM has also been used to optimise factors (temperature, pH, enzyme, and substrate loading) affecting enzymatic hydrolysis of Parthenium sp. (Pandiyan et al, 2014). Other tools like Taguchi have been used to optimise culture conditions for production of cellulases and xylanases by Phoma exigua on varying pH, surfactant, carbon and nitrogen sources (Tiwari et al, 2013).…”
Section: Discussionmentioning
confidence: 99%